Maintenance olaparib after platinum-based chemotherapy in patients with newly diagnosed advanced ovarian cancer and a BRCA mutation: efficacy by the timing of surgery and residual tumour status following upfront or interval cytoreductive surgery in the Phase III SOLO1 trial. (1st November 2019) - Moore, K; Colombo, N; Scambia, G; Kim, B-G; Oaknin, A; Friedlander, M; Lisyanskaya, A; Floquet, A; Leary, A; Sonke, GS; Gourley, C; Banerjee, S; et al.
Abstract : Introduction/Background: In SOLO1 (NCT01844986 ; GOG-3004), maintenance olaparib significantly improved progression-free survival (PFS) vs placebo (HR 0.30; 95% CI 0.23–0.41; P <0.0001; Moore et al. NEJM 2018) in patients with newly diagnosed advanced ovarian cancer (OC) and a BRCA mutation (BRCAm) who were in clinical complete response (CR) or partial response (PR) following platinum-based chemotherapy. This analysis evaluates olaparib efficacy in SOLO1 by timing of surgery and presence of residual tumour following surgery. Methodology: SOLO1 recruited patients who had undergone upfront or interval cytoreductive surgery and had no residual or residual macroscopic disease. Patients were stratified by platinum response (clinical CR or PR) and received olaparib tablets 300 mg twice daily or placebo. PFS was assessed by investigators using modified RECIST v1.1. Results: 260 patients were randomized to olaparib and 131 to placebo; one patient did not receive placebo. Median follow-up was 41 months in both arms. 63% and 35% of patients underwent upfront and interval surgery, respectively; 76% and 21% had no residual and residual macroscopic disease, respectively, after surgery regardless of timing; and 44% of SOLO1 patients had stage III disease, underwent upfront surgery and had no residual disease following surgery. PFS was significantly improved with olaparib, regardless of the timing of surgery or residual disease status after surgery (table 1 ). PFS was also significantly improved in the subgroup of patients with stage III disease who underwent upfront surgery and had no residual disease following surgery. Conclusion: Maintenance olaparib improved outcomes compared with placebo in patients with newly diagnosed advanced OC and a BRCAm, regardless of the timing of surgery or residual disease status after surgery. Olaparib improved PFS in stage III patients who had undergone upfront surgery and had no residual disease, a population at high risk of progression, but typically excluded from first-line OC trials. Disclosure: KM: Ad board: AZ, Advaxis, Clovis, Tesaro, Genentech/Roche, Immunogen, VBL Therapeutics, Merck, Janssen, Aravive, Pfizer, Eisai, Samumed, Oncomed. NC: Honoraria/reimbursement, speaker role/advisory board fees: AZ, Roche, Tesaro, PharmaMar; advisory board fees: Clovis, Pfizer. GS: None. B-GK: None. AO: Consulting fees: Roche, AZ, PharmaMar, Clovis, Tesaro, Immunogen, Genmab. MF: Honoraria, speaker role/advisory boards: AZ; advisory board fees: MSD, Lilly, Takeda; non-comp consulting: AbbVie. AL: None. AF: Advisory board fees: AZ, Clovis; congress support: Roche, PharmaMar; advisory board fees/congress support: Tesaro. AL: Honoraria/reimbursement, advisory board fees: AZ; advisory board fees: Clovis, Biocad; consulting fees: Seattle Genetics. GS: Research funding: AZ, Merck, Novartis, Roche. CG: Honoraria/reimbursement, consulting fees, grants: AZ, Tesaro, Nucana; honoraria/reimbursement, consulting fees: Roche, Clovis, Foundation One, MSD, Sierra Oncology; grants: Novartis, Aprea. SB: Grants, honoraria/reimbursement: AZ; honoraria/reimbursement: Tesaro, Clovis, Merck, PharmaMar, Roche, Seattle Genetics. AO: Steering committee role (non-comp): AZ, Clovis, Tesaro. AG-M: Speaker role/consulting fees: AZ, Tesaro, PharmaMar, Roche; consulting fees: Clovis, Inmunogen, Genmab, Pfizer, MSD. CA: Honoraria/reimbursement: Tesaro, ImmunoGen, Clovis. WB: None. CM: None. JL: Advisory board fees: AZ, Clovis, Mersana, Tesaro. ESL: Shareholder, employee: AZ. RB: Shareholder, employee: AZ. PD: Consulting fees: AZ, Tesaro.